The effects of bank competitions on liquidity risks and profit sustainability An applied study on Saudi banks for the period (2013-2020) - Abdul Rahman, Najla Ibrahim; Alnofaie, Raya Mohammed Ibraheem (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the effect of banks’ competition on Liquidity risks and profit sustainability. The study used competition as an independent variable, while the two dependent variables are liquidity risks and profit sustainability. The sample of the study consisted of eight commercial banks, and the period of the study was between (2013-2020). The study applied descriptive statistics, the Hausman test, and multiple linear regression to test the hypotheses. To measure the independent variable (competition) used Lerner index, as an indicator of market power. The study’s dependent variable of liquidity risks was measured by the liquidity risks of the bank’s traditional activities and modern activities. Profit sustainability as the dependent variable was measured by income diversification, return on assets, and return on equity, in order to achieve the main goal of knowing the effect of bank competition on liquidity risks and profit sustainability, through six subs-hypotheses. The study indicates that there is a significant positive impact of the Lerner index has been found at a low level on liquidity risks (liquidity assets ratio). Moreover, a negative significant impact of the Lerner index on income diversification indicator, and a positive significant impact of it on income type (Interest income, non-interest income) was founded. Thus, the bank’s low competition level increases the bank’s profitability. The study indicates that there is a significant negative impact of liquidity risks (employment ratio of traditional activities) on income diversification, return on assets, and return on equity. In addition, a positive significant impact of liquidity risks (liquidity assets ratio) on return on assets, while a negative significant impact on return on equity. Furthermore, the study shows that commercial banks exceed the minimum standard of Basel III liquidity ratios requirements of the liquidity coverage ratio (LCR), and net stable funding ratio (NSFR). The study recommends enhancing banks’ profit and minimizing liquidity surplus to achieve a high return on assets, and return on equity by the expansion of banks’ activities. Commercial banks need to increase profitability to support their sustainability to enhance and maintain banks' financial position.
Keywords: Competition; financial risks; Profit sustainability; liquidity risks; commercial Banks